Monitoring at the CO2 SINK site: A concept integrating geophysics, geochemistry and microbiology - Giese, R.; Henninges, J.; Lüth, S.; Morozova, D.; Schmidt-Hattenberger, C.; Würdemann, H.; Zimmer, M.; Cosma, C.; Juhlin, Christopher (2009)
At the CO2SINK site (Ketzin, near Berlin, Germany), the pilot study for onshore CO2 storage in saline aquifers includes monitoring of the storage reservoir and the structures above using physical, chemical, and microbial observations. Seismic and geoelectric measurements have delivered the structural framework and monitor CO2 propagation between two observation wells. Borehole temperature data serves to derive information about in-situ formation temperatures and to detect processes related to the injection and movement of CO2 in the subsurface. Pressure measurements aim at ensuring safe operations and characterization of the reservoir. For a complete characterization of the CO2 storage process, the physical observations have to be complemented by chemical and biological probing, as fluid/fluid and fluid/rock interactions and microbial processes play an important role possibly affecting the stability of the reservoir and caprock. A newly developed Gas Membrane Sensor detected the CO2 breakthrough on the first monitoring well. Microbial investigations contributed in optimizing the injection borehole after recognizing organisms reducing its injectivity. © 2009 Elsevier Ltd. All rights reserved.